Measurement Ratio of 226Ra/228Ra in Marine Samples Using The Cation Exchange Resin and Gross α/β Spectrometry - ABD RAHIM MOHAMED, CHE; SIEW YEW, NIOO; MOHD ALI, MASNI; BIN AHMAD, ZAHARUDIN (Asian Journal of Chemistry, 2010)
A method for determine activity of 226Ra and 228Ra in seawater samples by Gross α/β spectrometry was developed, where the Ba(Ra) was purified using a cation exchange resin column in warm temperature (70ºC). The Ba(Ra)SO4 salts were wrapped on the plastic disc and counted using the gross α/β spectrometry after remain standing for three months. In order to certify the validation of this method, sediment reference materials have been analyzed and provided a good agreement between the analytical results and recommended values with the recovery values of 105.2 and 108.5% for 226Ra and 228Ra, respectively. This radiochemical procedure was also applied on the marine environment samples collected from Pulau Redang, Terengganu, such as seawater and suspended particulate matter. The analytical results for 226Ra and 228Ra in seawater were varied from 2.08 ± 0.19 mBq L-1 to 12.43 ± 0.47 mBq L-1 and 5.92 ± 0.93 mBq L-1 to 33.53 ± 2.03 mBq L-1, respectively. Meanwhile, the activities of 226Ra and 228Ra in suspended particulate matter were also varied in the range of 4.32 ± 0.37 Bq g-1 to10.29 ± 0.59 Bq g-1 and 5.12 ± 0.46 Bq g-1 to 9.82 ± 0.47 Bq g-1, respectively.